Revision Arthroscopic Bankart Repair in the Military. Issue 3 (27th March 2020) - Slaven, Sean E.; Tardif, Robert; Foley, Kevin; Cameron, Kenneth L.; Posner, Matthew A.; Dickens, Jonathan F.
Objectives: There is no consensus on the optimal method of stabilization (arthroscopic or open) for revision anterior shoulder stabilization. The purpose of this study was to determine the success of revision arthroscopic stabilization at preventing further recurrence in active duty military patients. Methods: 53 revision arthroscopic stabilizations were performed at our institution between 2005-2016 for recurrent anterior shoulder instability after an arthroscopic Bankart index procedure. Shoulders with glenoid bone loss >20% were excluded from the study. The primary outcome of interest was the ability to return to activity/duty without subsequent instability. Patients were followed for time to a subsequent instability event and repeat revision arthroscopic stabilization following return to duty/activity. Results: Patient age at revision surgery averaged 22.9 ± 4.3 years. Mean follow up was 6.1 years (range 0.4-12.9). 34 out of 53 patients (64%) returned to duty without recurrent instability following revision arthroscopic anterior stabilization. 19 patients (36%) experienced recurrent instability following return to duty after revision arthroscopic stabilization. Glenoid bone loss averaged 7.8% ± 8.0% in the successful group and 6.5 % ± 6.5% in the failure group (p=0.573). Durability of the index surgery was significantly longer in the successful group (38.1 ± 31.3 months vs. 20.5 ± 17.8 months, p=.029). There was no difference between groups in patient age or number of anchors used in the index or revision stabilization procedures. Conclusion: Revision arthroscopic stabilization of failed primary arthroscopic Bankart repair has a failure rate of 36% in a young active duty military population, which is substantially higher than primary arthroscopic Bankart repair in this population and higher than revision arthroscopic Bankart repair in other patient populations. The similar amounts of bone loss between groups indicates that bone loss is not the primary determinant of failure in revision arthroscopic stabilization.